Kingdom hearts 358/2 days. 4 - Amano, Shiro (Yen Press, 2014)
"Left alone to ponder the purpose of her existence and desperate for answers, Xion journeys alone to find out who<U+2013>or what<U+2013>she really is. But little do she, Roxas, and Axel know that her quest will lead to the close of one tale and the continuation of another<U+2026>"- publisher's website.